London's Hadrianic War?. (November 2017) - Perring, Dominic
ABSTRACT: Recent work has advanced our understanding of human crania found in London's upper Walbrook valley, where skull deposition appears to have peaked during the occupation of the Cripplegate fort, itself probably built soon after London's Hadrianic fire. Although this fire is usually considered to have been accidental, parallels can be drawn with London's Boudican destruction. This article explores the possibility that these three strands of Hadrianic evidence — fire, fort and skulls — find common explanation in events associated with a British war of this period. This might support the identification of some Walbrook skulls as trophy heads, disposed as noxii in wet places in the urban pomerium .